Allosteric modulation of α7 nicotinic receptors by flavonoids - Nielsen, Beatriz Elizabeth (2018)
Plants have emerged as a valuable source for neuroprotective compounds like flavonoids. These polyphenolic com pounds decrease neurotoxicity and the development of neurodegeneration. Potentiation of α7 nicotinic receptor, which is involved in cognition and memory, is a potential therapeu tic strategy in neurodegenerative disorders. In particular, positive allosteric modulators (PAMs) are emerging as the best therapeutic tools. Some flavonoids have been reported as ligands for α7 , but the molecular mechanisms underlying this interaction remain unknown. Our main goal is to unrav el the molecular basis of flavonoid action at α7 by electro physiological techniques. We analyzed the effects of prototypes of distinct classes of flavonoids: quercetin, genistein, and 7-dihydroxy-4-phenylcoumarin (neoflavonoid) on α7 activity. At the macroscopic level, the three compounds increased the peak current elicited by acetylcholine with minimal effects on desensitization, indicating that they behave as type I PAMs. At the single-channel level, they increased, with different efficacies, the duration of the open state. By analyzing the effects of flavonoids on mutant and chimeric α7 receptors, we found that they share the transmembrane structural determinants of poten tiation known for other PAMs. We conclude that, in addition to the well-known effects as antioxidants, the unique properties of flavonoids as natural α7 PAMs make them candidate compounds for the treatment of neurodegenerative disorders.